Rising asthma admissions and self referral. Issue 7 (July 1988) - Storr, J; Barrell, E; Lenney, W
Abstract : An eight fold rise in asthma admissions to the Royal Alexandra Hospital for Sick Children, Brighton occurred over the 15 year period 1971-85. The cause was an increase in the number of children seen, rather than increased readmission. The initial rise was associated with the introduction of nebulised salbutamol in 1976. The children concerned were mainly over 5 years old. Three years later came a larger influx of younger children. Circumstances leading to admissions were examined in a prospective study over a one year period. There were 605 admissions, 437 (72%) were self referrals. The commonest reason parents gave for preferring hospital treatment was the availability of nebuliser treatment.